Pelatihan Pengembangan Ekosistem Digital Berbasis Blockchain-NFC untuk Peningkatan Literasi Keuangan dan Pengelolaan Karir Generasi Z di Era Society 5.0 - Almadany, Khairunnisa; Br Lubis, Ika Rahmadani; Rahmah, Maulidya (Jurnal Masyarakat Indonesia (Jumas), 2025)
In the era of Society 5.0, Generation Z is faced with new challenges in financial literacy and career management. This research aims to develop a digital ecosystem based on Blockchain technology and NFC (Near Field Communication) as a solution to enhance financial literacy and career management for Generation Z. Through specially designed training, participants will gain a better understanding of digital financial concepts and how to leverage technology for career development. The outcomes of this training are expected to have a positive impact on participants' abilities to manage their finances and plan their careers in the future.